Bioprospecção de metabólitos bioativos por abordagem genômica - Siqueira, Kátia Aparecida de (2021)
Endophytes are microorganisms that inhabit internal tissues of their hosts without showing visible symptoms of infection. They produce compounds with different biotechnological applications that can benefit the host plant. Despite increasing discoveries of new compounds synthesized by endophytes, there is a gap in knowledge about the biosynthetic pathways responsible for the production of bioactive metabolites. In this work, the genomes of the isolates Streptomyces griseocarneus-132, Pantoea coffeiphila-342, Pseudomonas plecoglossicida-382, Acinetobacter baumannii-I43, Curvularia geniculata-P1 and Aspergilllus sp. A31.The total genome sequencing was performed on an Illumina HiSeq4000 platform, paired-end mode, the assembler used was the Spades software. Subsequently, the fungi C. geniculata P1 and Aspergillus sp. A31 were cultivated and inoculated on Oryza sativa L. plants that grew in humid environments contaminated by mercury. The crude extract of the actinobacterium S. griseocarneus R132 was fractionated on a C18 silica column and the antimicrobial activity of the isolated metabolites was evaluated in vitro by disk diffusion and by RTqPCR in Galleria mellonella larvae. The total genome size ranged from 4,52 Mb (A. baumannii-I43) to 33.65 Mb (C. geniculata-P1). Aspergillus sp. A31 and C. geniculata P1 mitigated mercury toxicity and promoted the growth of host plants when inoculated with O. sativa. Through the 1H and 13C NMR analyses, it was possible to propose that the substances isolated from S. griseocarneus R132 are cinnamic acid and 4-chloro cinnamic acid. In the antimicrobial activity in vivo, treatments increased the survival and modulated the immune system of larvae infected with pathogenic microorganisms, between 60% and 80% of larvae were killed compared with the high survival observed in groups treated with fraction/substance. In Shell analyzes using the Antismash platform revealed the presence of clusters related to polyketide synthase (PKS) biosynthesis, NRPS, terpenes, Lantipeptide, hybrid pks-Nrps and bacteriocins. This study will help in the research of metabolic engineering of endophytic microorganism strains and their use in biotechnology.